A Retrospective Epidemiological Study of Rhinosporidiosis in a Rural Tertiary Care Centre in Pondicherry - Karthikeyan, P. (J Clin Diagn Res, 2016)
INTRODUCTION: Rhinosporidiosis is an age old endemic scourge which has affected various parts of the world, most notably India and Sri Lanka. Although a large body of literature exists regarding this problem, postoperative recurrence rates continue to vary, and the effect of public health education in the eradication of this disease has not been taken into account. AIM: The aim of this study was to find out the site, presentation and postoperative recurrence rate in patients with rhinosporidiosis. MATERIALS AND METHODS: This was a retrospective study involving operated cases of rhinosporidiosis in the Department of Ear, Nose and Throat of a rural tertiary care referral centre over a period of 3 years. The behavioural pattern of the disease, its epidemiology, rate of recurrence and outcomes of surgical management were analysed. RESULTS: A statistically significant correlation could be found between male gender and rural residential status and incidence of rhinosporidiosis. Bathing in rivers and ponds were found to be strongly associated with rhinosporidiosis (p=0.005). Almost all patients were found to be of low socioeconomic status. Nasal obstruction and epistaxis were the most common presenting complaints. CONCLUSION: Rhinosporidiosis is strongly associated with male gender, young and middle aged adults, agricultural occupations, rural residential status, a history of bathing in ponds and rivers and a low socioeconomic status. Post-surgical recurrence of rhinosporidial masses can be avoided with careful and complete clearance of the mass and cauterization of the base. Appropriate and consistent public health education helps to reduce the incidence of rhinosporidiosis in endemic communities.